Wolbachia Endobacteria in Natural Populations of Culex pipiens of Iran and Its Phylogenetic Congruence - Karami, Mohsen (J Arthropod Borne Dis, 2016)
BACKGROUND: Wolbachia are common intracellular bacteria that infect different groups of arthropods including mosquitoes. These bacteria modify host biology and may induce feminization, parthenogenesis, male killing and cytoplasmic incompatibility (CI). Recently Wolbachia is being nominated as a bio-agent and paratransgenic candidate to control mosquito borne diseases. METHODS: Here we report the results of a survey for presence, frequency, and phylogenetic congruence of these endosymbiont bacteria in Culex pipiens populations in Northern, Central, and Southern parts of Iran using nested-PCR amplification of wsp gene. RESULTS: Wolbachia DNA were found in 227 (87.3%) out of 260 wild-caught mosquitoes. The rate of infection in adult females ranged from 61.5% to 100%, while in males were from 80% to 100%. The Blast search and phylogenetic analysis of the wsp gene sequence revealed that the Wolbachia strain from Iranian Cx. pipiens was identical to the Wolbachia strains of supergroup B previously reported in members of the Cx. pipiens complex. They had also identical sequence homology with the Wolbachia strains from a group of distinct arthropods including lepidopteran, wasps, flies, damselfly, thrips, and mites from remote geographical areas of the world. CONCLUSION: It is suggested that Wolbachia strains horizontally transfer between unrelated host organisms over evolutionary time. Also results of this study indicates that Wolbachia infections were highly prevalent infecting all Cx. pipiens populations throughout the country, however further study needs to define Wolbachia inter-population reproductive incompatibility pattern and its usefulness as a bio-agent control measure.